Negotiating Water and Technology—Competing Expectations and Confronting Knowledges in the Case of the Coca Codo Sinclair in Ecuador - Teräväinen, Tuula (Water (Basel), 2019)
Recent and on-going mega-hydraulic development in the global South implies profound socio-technical, ecological, territorial and cultural transformations at different levels and spaces of society. The transformations often involve conflicts and also new governance arrangements between different knowledge regimes, local practices and national and global frameworks of climate mitigation, water resources management and the green economy. Significantly, they also entail varying expectations concerning the meaning of water and the political promises of technology in advancing more sustainable futures. Drawing on sociological science and technology studies, particularly the sociology of expectations, this article analyses competing, parallel and confronting expectations regarding water and technology that different actors produce, negotiate and contest in the context of the recently launched 1500 MW hydropower megaproject Coca Codo Sinclair in Ecuador. It takes expectations as performative as they may shape and challenge policies, discourses, social interactions, institutions and power relations. By analysing and comparing these expectations, the article scrutinises the socio-technical imaginaries and related knowledge regimes they represent, derive from and support, and what kinds of repercussions these have in terms of water resources management in particular and sustainability governance in general.